Association between provincial income levels and drug prices in China over the period 2010–2017. (October 2020) - Shi, Wunan; Wouters, Olivier J.; Liu, Gordon; Mossialos, Elias; Yang, Xiuyun
Abstract: In the past decade, the Chinese central government has made sweeping reforms to national pharmaceutical policies. However, provincial authorities have retained control over most drug procurement procedures, potentially leading to cross-province differences in drug prices. The objectives of this study were to (i) examine drug price trends in 31 Chinese provinces and municipalities between 2010 and 2017; (ii) evaluate the association between provincial income levels and drug prices over this period; and (iii) compare the results for Chinese state-owned, Chinese private, and multinational pharmaceutical firms. Using publicly available data on procurement prices of the drugs manufactured by the top 30 pharmaceutical firms in China (in terms of revenues), we ran a generalized country-product-dummy regression to compare drug prices across provinces over the study period. We conducted subgroup analyses to test for differences between types of firms. Between 2010 and 2017, drug prices decreased by an average of 23% across the country. The prices of drugs sold by multinational firms dropped by 32% over this period, while the prices of drugs sold by Chinese private firms declined by 28%. By contrast, the drug prices of state-owned firms went up by 11%. There were statistically significant positive associations between drug prices and provincial income levels for the full sample in 2010, 2011, and 2013. There were no significant associations in other years. Several low-income provinces paid higher procurement prices than some high-income provinces for identical medicines, especially in later study years. The lack of association between income levels and prices poses equity concerns and may place a heavier cost burden on the poor. It also suggests that China's pharmaceutical policies may be failing to balance the dual aims of drug affordability and incentives for innovation. Highlights: Drug procurement prices dropped by an average of 23% between 2010 and 2017 in China. Trends in prices varied between drugs sold by different types of firms. There was no association between prices and provincial incomes in most years. This may have placed a heavier cost burden on poorer provinces.